Mergers and acquisitions: managing the IT perspective - Jørgensen, Thomas (Henry Stewart Talks, 2020)
Types and scope of M&A engagements, How the M&A process affects business, Day 1 Planning, Day 100 Planning, Executing a company merger, Workstream and plans for company mergers